O Epistológrafo Personagem: O Olhar Dos Editores Sobre As Cartas De Álvares De Azevedo - Rodrigues, Vanessa Neri [UNIFESP] (2018)
The Years That Comprehended The Short Life Of The Poet Álvares De Azevedo Was A Period Of Political, Social, Economic And Cultural Effervescence In The History Of Brazil, Factors That Made His Works And Life Trajectory Target Of Several Readings Over Time. The Correspondence Exchanged, Especially With His Mother, Written Within 1840 And 1851, During The Displacement Of Álvares De Azevedo Between The Cities Of Rio De Janeiro And São Paulo, Constitutes An Important Set Of Documents Not Only To Possibly Understand The Author As A Social Man, Who Had His Trajectories And Experiences Expressed In His Letters, But Also To Question The Importance Of Assembling, Organizing And Publishing These Correspondences. When We Look At The Main Issues Which Present Them, We Seek To Understand The Figure Of The Organizer, The Trajectory Of These Documents And Their Context Of Publication. At The Same Time, This Lecture Aims To Analyze And Comprehend The Structure Of The Editions, Their Gaps And Marks Left By The Editors, Trying